Dampak Kebijakan Ekonomi Syariah terhadap Stabilitas Makroekonomi di Indonesia - Alam Mudawwam Bakhroni; Madian Muhammad Muchlis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the contribution of Islamic economic policies to macroeconomic stability in Indonesia through various Islamic financial instruments. The results show that Islamic economic policies, including Islamic banking, zakat, waqf, and sukuk, play a significant role in supporting economic stability and fostering real sector growth. Profit-sharing financing offered by Islamic banking, for instance, provides a fairer and more flexible alternative compared to conventional systems. Furthermore, wealth redistribution instruments such as zakat and productive waqf have proven to help reduce poverty and improve community welfare. However, challenges remain regarding the low financial literacy of Islamic finance and the lack of infrastructure supporting its implementation. This study suggests the need for strategic steps to strengthen Islamic financial literacy, enhance digital technology, and strengthen collaboration between the government, Islamic financial institutions, and society in promoting inclusive and sustainable Islamic economic growth.